Avaliação ecotoxicológica preliminar das águas das bacias hidrográficas dos rios Tarumã, São Raimundo e Educandos - Rodrigues, Déborah Oliveira; Silva, Sergio Luiz Rodrigues da; Silva, Maria do Socorro Rocha da (Acta Amazonica, 2009)
The Tarumã, São Raimundo and Educandos basins, and their tributaries, are impacted by antropic influence. This study tried to evaluate the water toxicity of the hydrographic basins, through acute toxicity bioassay using Daphnia similis as test-organism and physical and chemical analysis. The results showed that, of the three basins, the water from Tarumã caused the most deleterious effect on D. similis.
Preliminary evaluation of the toxicity in water of the Tarumã, São Raimundo and Educandos basins
Keywords: Eco-toxicology; Acute Toxicity; Daphnia Similis; Ecotoxicologia; Toxicidade Aguda; Daphnia Similis